Learning Agenda on Gender and Climate Smart Agriculture: Draft Theory of Change - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
his document presents a working Theory of Change (TOC) co-created as part of CGIAR’s Generating Evidence and New Directions for Equitable Results (GENDER) Platform’s ongoing process to develop a Learning Agenda (LA) focused on Climate Smart Agriculture (CSA) and gender equality. The LA is intended to define priority learning questions jointly developed by key stakeholders, and identify potential learning activities, capacity needs and communication products. The goal is to activate stakeholders across the CGIAR and its partners to learn collectively with a focus on identified and prioritized knowledge gaps in research for development (R4D) on CSA and gender.